The Question of Commissioning Fees in the us: A Composer’s Perspective - Wiprud, Theodore (Circuit, 2016)
Active professional composers of concert and dramatic music continue to rely on commissions as an important source of income. Theodore Wiprud, a composer and senior arts administrator, examines how the sources and distribution of commissions has evolved in recent years in United States. A range of working composers discuss their experiences and how the nature of a given commission can affect everything from the creative process to a new work’s reception and performance opportunities.